KOMUNIKASI ORGANISASI, KEPEMIMPINAN, DAN KOMUNIKASI POLITIK: SATU TAHUN KINERJA KABINET MERAH PUTIH - Riyadi, Ilham (Communication and Islamic Broadcasting Studies IAIN Parepare, 2025)
This study aims to analyze the interrelation between bureaucratic communication systems, leadership styles, and the effectiveness of government political communication during the first year of the Merah Putih Cabinet. Using a qualitative approach and a literature review method, this research draws upon previous studies, national research institute reports, and official government data. The analysis is conducted through thematic and interpretive comparison of organizational communication theories and political communication theories. The findings indicate that although the Prabowo–Gibran administration has succeeded in maintaining political stability and achieving positive economic growth, communication effectiveness across government institutions and consistency in public messaging remain significant challenges. Communication incongruence between ministries reflects weak horizontal bureaucratic coordination. From a political communication perspective, frequent spontaneous and controversial public statements by key government officials including the President have not strengthened public trust; instead, they reveal issues of insensitivity and highlight hierarchical power dynamics in policy‐making. In summary, this article identifies five key communication issues in the Merah Putih Cabinet: misaligned government agenda setting, technocratic communication delivered out of context, echo chamber tendencies leading to tone‐deaf messaging, reliance on the magic bullet paradigm viewing the public as passive recipients, and concerns regarding transparency and credibility of officials. Therefore, it is essential for the government to strengthen a national communication strategy that fosters two‐way communication between the state and the public.